First Principle Study of Defect Induced Band Structure in Cu Substituted Bi2Te3 Topological Insulator - Dan S.; Pal D.; Patil S. (My University, 2025)
This paper deals with the Cu substituted Bi2Te3 topological insulator's electronic band structure and its defect induced behavior. The pristine Bi2Te3 compound has a unique band structure, where the bulk band is semiconducting and the surface band is metallic. However, here, we report the modulation of the bulk-band structure with the injection of Cu atoms in the pristine Bi2Te3 compound. Our ab initio simulation reveals that 5 at.% of Cu substitution in Bi site transforms the electronic ground state of Bi2Te3 to a p-type one. In contrast, the intercalation of Cu atoms by a similar amount turns the electronic ground state of Bi2Te3 into an n-type one. We have also discussed the band structure of the carrier-compensated configuration of the Cu substituted Bi2Te3 compound with the creation of Te vacancy. Our simulation gives an excellent agreement with the experimentally. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.